Dual spherical electric field strength sensors with separate sensitive elements and their research - S. V. Biryukov; S. S. Kolmogorova (Омский научный вестник)
A new type of electric induction spherical electric field strength sensors is being investigated, which is classified according to the newly introduced classification feature - to dual sensors. The paper focuses on the study of dual sensors with separate sensitive elements. As a result of the study, a relationship is obtained between the angular dimensions of the sensing elements of a dual sensor and its error due to field inhomogeneity maintained in the maximum possible spatial measurement range. This relationship formed the basis for constructing a mathematical model of the dual sensor, which made it possible to identify the ranges of angular sizes of the sensitive elements of the sensor and its errors due to the inhomogeneity of the electric field. The range of set angular dimensions of the sensing elements of the first double sensor is 35,531 33,53 and the second double sensor is 35,532 85 at 3 =90 and the corresponding error range is  ±0,78 %  ±9,12 % and spatial measurement range 0<a<1. The results of the conducted studies show the promise of using dual sensors with composite sensitive elements.